Efficacy and safety of preoperative embolization in surgical treatment of brain arteriovenous malformations: a multicentre study with propensity score matching - Salim, Hamza; Hamdan, Dawoud; Adeeb, Nimer; Kandregula, Sandeep; Aslan, Assala; Musmar, Basel; Ogilvy, Christopher S.; Dmytriw, Adam A.; Abdelsalam, Ahmed; Ataoglu, Cagdas; Erginoglu, Ufuk; Kondziolka, Douglas; et al. (Journal of neurology, neurosurgery, and psychiatry, 2025)
Background Brain arteriovenous malformations (AVMs) are abnormal connections between feeding arteries and draining veins, associated with significant risks of haemorrhage, seizures and other neurological deficits. Preoperative embolization is commonly used as an adjunct to microsurgical resection, with the aim of reducing intraoperative complications and improving outcomes. However, the efficacy and safety of this approach remain controversial. - Methods This study is a subanalysis of the Multicenter International Study for Treatment of Brain AVMs consortium. We retrospectively analysed 486 patients with brain AVMs treated with microsurgical resection between January 2010 and December 2023. Patients were divided into two groups: those who underwent microsurgery alone (n=245) and those who received preoperative embolization, followed by microsurgery (n=241). Propensity score matching was employed, resulting in 288 matched patients (144 in each group). The primary outcomes were rates of complete AVM obliteration and functional outcomes (measured by the modified Rankin Scale (mRS)). Secondary outcomes included complication rates, mortality, hospital length of stay and postsurgical rupture. - Results After matching, the complete obliteration rate was 97% with no significant difference between the microsurgery-only group and the preoperative embolization group (p=0.12). The proportion of patients with an mRS score of 0-2 at the last follow-up was similar in both groups (83% vs 84%; p=0.67). The median hospital stay was significantly longer for the embolisation group (9 days vs 7 days; p=0.017). Complication rates (24% vs 22%; p=0.57) and mortality rates (4.9% vs 2.1%; p=0.20) were comparable between the two groups. No significant differences were observed in postsurgical rupture, recurrence or retreatment rates. - Conclusions In this large multicentre study, preoperative embolization did not significantly improve AVM obliteration rates, functional outcomes or reduce complications compared with microsurgery alone.
Zuerst veröffentlicht: 6. Februar 2025
Gesehen am 06.08.2025